Mnemonic capabilities: Collective memory as a dynamic capability - Diego M. Coraiola; Roy Suddaby; William M. Foster (RAE: Revista de Administração de Empresas, 2017)
Dynamic capabilities (DCs) are the processes that organizations develop to remain competitive over time. However, in spite of the importance of temporality in the development of DCs, the roles of time, history, and memory remain largely implicit. In fact, most studies focus on the past as a source of constraints and limits for managerial action. Alternatively, we advocate for a social constructionist view of the past. Our core argument is that the capacity to manage the past is a critical competence of modern organizations. We argue that organizations can manage their collective memory as resources that aid the objective reproduction and exploitation of existing routines, the interpretive reconstruction and recombination of past capabilities for adaptation to environmental change, and the imaginative extension and exploration of collective memory for anticipated scenarios and outcomes. This renewed view of time, history, and memory is better suited for a dynamic theory of competitive advantage.